Post Office Engineering Union - Branch minute book, 1966 (London, 1966)
1966 1961-70 "Post Office Engineering Union - Branch minute book, 1966" [BW0147], 1966, Trades Union Congress This minute book records the meetings of the London Postal Railway Branch of the Post Office Engineering Union 1964-1968